2013
DOI: 10.1063/1.4805048
|View full text |Cite
|
Sign up to set email alerts
|

Coercivity enhancement of anisotropic die-upset Nd-Fe-B powders by Pr-Cu alloy diffusion

Abstract: The grain boundary diffusion treatment using the low melting point Pr-Cu eutectic alloy was applied to enhance the coercivity of anisotropic die-upset Nd-Fe-B powders. It was found that the room temperature coercivity of the powders increases from 13 kOe to 24 kOe. The thickness of the grain boundary layer was increased and the Fe and Co content in the grain boundary phases was decreased. The modified boundary layers may thus increase the domain wall nucleation field, leading to an enhancement in the coercivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…From the XRD peaks it is also evident that the volume fraction of α-Fe phase decreased upon infiltration in both ribbons and deformed magnets. The decrease in α-Fe phase could be attributed to the reaction of Pr 75 (Cu 0.25 Co 0.75 ) 25 phase with α-Fe phase forming Prrich phase containing Fe resulting in the decrease of α-Fe content.Similar observations were made by Wan et al[9] in MQA powders infiltrated by Pr-Cu alloy from XRD and microscopy studies. Tang et al[8] also reported a decrease in α-Fe phase content in Nd 90 Cu 10 grain boundary diffused MQP-15-7 hot-deformed magnet.Fig.…”
supporting
confidence: 85%
See 2 more Smart Citations
“…From the XRD peaks it is also evident that the volume fraction of α-Fe phase decreased upon infiltration in both ribbons and deformed magnets. The decrease in α-Fe phase could be attributed to the reaction of Pr 75 (Cu 0.25 Co 0.75 ) 25 phase with α-Fe phase forming Prrich phase containing Fe resulting in the decrease of α-Fe content.Similar observations were made by Wan et al[9] in MQA powders infiltrated by Pr-Cu alloy from XRD and microscopy studies. Tang et al[8] also reported a decrease in α-Fe phase content in Nd 90 Cu 10 grain boundary diffused MQP-15-7 hot-deformed magnet.Fig.…”
supporting
confidence: 85%
“…The decreased susceptibility here after suggests that the domain walls are pinned at grain boundaries. When field higher than the pinning force is applied the remaining magnetic reversal occurs by the depinning of the magnetic domain walls [9,13,14].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such diffusion treatment has been tested in hydrogenation-disproportionation-desorptionrecombination (HDDR) powders, melt-spin ribbons, hot-deformed magnets, etc., and has been proven to be very effective in coercivity improvement. [17][18][19][20][21][22][23][24] Therefore, we extend this diffusion (doping) technique into sintered magnets.…”
Section: Introductionmentioning
confidence: 99%
“…[http://dx.doi.org/10.1063/1.4886767] Recently, grain boundary diffusion (GBD) process has been applied to different kinds of Nd-based permanent magnets and exhibited significant enhancement in intrinsic coercivity (H cj ) without obvious reduction in remanence (B r ). [1][2][3][4][5][6][7][8][9] In the GBD process, Dy or Tb element in alloy powders, compound powders, or metallic vapor are supplied to the surface of the magnets and then diffuse into the magnets through the grain boundary phase during the heat treatment. With GBD treatment, the application of limited and expensive rare earth resources, such as Dy or Tb, can be optimized.…”
mentioning
confidence: 99%